Does the use of Digital Marketing Communication Strategy Effectively Affect Conversions? (Case Study on DatascripMall.ID) - Alfiyahsari, Rifqi; Taurina, RA Christanti; Priyanka, Glenis (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The development of technology, it then has a significant impact on aspects of human life and also business development. In this case, there are many methods that can be used as a method of using digital marketing strategies for companies. In this study, a cash study was taken on DatascripMall.id whose line of business is in the technology sector. The research method used this time is a quantitative research method with data collection techniques using primary and secondary methods. The results obtained in this study is that there is a significant influence between each variable on the company related to efforts to increase company profits.